Empowering Creativity: Enhancing Creative Writing Skills through Pixton in Community Service Initiatives - Dangin Dangin; Elysa Hartati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This community service project investigates the transformative potential of Pixton, a digital comic creation tool, in fostering creative writing skills within a community setting. The initiative seeks to empower individuals through engaging workshops that leverage Pixton as a means to unlock and express creativity. Utilizing a participatory action research approach, the project assesses both the quantitative progress in creative writing proficiency and the qualitative impact on participants' engagement and self-expression. The workshops are designed to provide a supportive space for community members to explore their narrative voices using Pixton, encouraging collaborative storytelling. Through a synthesis of pre and post-assessment data, reflective journals, and participant interviews, the project aims to contribute valuable insights into the role of digital tools in community-based creative initiatives, ultimately fostering a sense of empowerment, expression, and community cohesion.